DERMATOGLYPHICS IN PRIMARY HYPERTENSIVE PATIENTS - SRI KRISHNA GANESH KULKARNI,; AVINASH SS,; SREEKANTHA,; REMYA,; VINODCHANDRAN, (International Journal of Pharma and Bio Sciences, 2014)
Dermatoglyphics is influenced by heredity and abnormality in it are associated with chromosomal anamolies. Primary hypertension is polygenic and the scientific dermatoglyphic pattern analysis are rare, which could be used as a diagnostic and screening aid.The present was done to study the frequency distribution of scientific ridge pattern in primary hypertensives.The study was carried out in 200 primary hypertensives with 200 normal controls. The hand imprinting was done using a slight modification of conventional ink flab method. Data were analysed using t test.The primary hypertensive male and female had significantly high frequency of whorls and TFRC and decreased ulnar loops and "atd" angle in both hands.Dermatoglyphics can be considered as a simple, inexpensive aid for screening and diagnosing primary hypertension.